Multilinear Fractional Integral Operators on Morrey Spaces with Variable Exponent on Bounded Domain (Communications in Mathematical Research, 2021)
We prove the boundedness of multilinear fractional integral operators onproducts of the variable exponent Morrey spaces on bounded domain.